Application of Non-Gluten Canistel (Pouteria campechiana) Flour-Maizena-Mocaf-Tapioca Composite on the Processing of Steamed Brownies - Sri Rejeki Retna Pertiwi; Aminullah Aminullah; Rosy Hutami; Deti Nirmala (Universitas Djuanda, 2018)
This study was aimed to analyze the effect of non-gluten composite and pan size on the quality of steamed brownies. Steamed brownies were prepared with three different non-gluten composites (campolay flour-maizena, campolay flour-mocaf, campolay flour-tapioca) in the proportion of 1:1 and baked in three different pan size (S: 20 cm x 7 cm, M: 22 cm x 9 cm, L: 24 cm x 11 cm). Analysis included physical properties (rising index, spesific volume, hardness, crumb appearance), sensory properties and acceptance, as well as chemical properties for the best steamed brownies. The data were analyzed using ANOVA and the results showed that non-gluten composite, pan size, and interaction of both factors effected significantly some physical properties, sensory properties and acceptance of steamed brownies. The best steamed brownies was the brownies made from non-gluten composite campolay flour-mocaf 1:1 with pan size S (20 cm x 7 cm). The best brownies contained moisture 21,55 %, ash 1,28 %, protein 4,16 %, fat 22,55 %, carbohydrate 50,45 %, dietary fiber 1,75 %, energy 421,39 kcal/100 g, and betacarotene 1,11 mg/100g. Key words: campolay flour, composite, non-gluten, steamed brownies.